The impact of large-scale social protection interventions on grain prices in poor countries: Evidence from Ethiopia - Hoddinott, John F.; Stifel, David; Hirvonen, Kalle; Minten, Bart (International Food Policy Research Institute, 2018)
There has long been concern that cash and in-kind transfers might affect prices in developing country food markets. While there have been a number of studies at highly aggregated levels, much less is known about the effects of cash transfers on local food prices and even less about how they compare to food transfers. We consider this issue in the context of a large social protection intervention, Ethiopia’s Productive Safety Net Programme. Using 12 months of price data from 233 localities and controlling for temporal, location, and market characteristics we find: Cash transfers have no effect on food prices. There is some evidence that food transfers reduce food prices. Maize transfers reduce aggregate grain prices, wheat transfers reduce the price of maize, and the negative effect of food transfers on food prices is larger in more remote markets. However, the magnitudes of these effects are trivially small, both in absolute and percentage terms.